DEFORMATION WAVES AS A TRIGGER MECHANISM OF SEISMIC ACTIVITY IN SEISMIC ZONES OF THE CONTINENTAL LITHOSPHERE - S. I. Sherman (Геодинамика и тектонофизика)
Deformation waves as a trigger mechanism of seismic activity and migration of earthquake foci have been under discussion by researchers in seismology and geodynamics for over 50 years. Four sections of this article present available principal data on impacts of wave processes on seismicity and new data. The first section reviews analytical and experimental studies aimed at identification of relationships between wave processes in the lithosphere and seismic activity manifested as space-and-time migration of individual earthquake foci or clusters of earthquakes. It is concluded that with a systematic approach, instead of using a variety of terms to denote waves that trigger seismic process in the lithosphere, it is reasonable to apply the concise definition of ‘deformation waves’, which is most often used in fact.The second section contains a description of deformation waves considered as the trigger mechanism of seismic activity. It is concluded that a variety of methods are applied to identify deformation waves, and such methods are based on various research methods and concepts that naturally differ in sensitivity concerning detection of waves and/or impact of the waves on seismic process. Epicenters of strong earthquakes are grouped into specific linear or arc-shaped systems, which common criterion is the same time interval of the occurrence of events under analysis. On site the systems compose zones with similar time sequences, which correspond to the physical notion of moving waves (Fig. 9). Periods of manifestation of such waves are estimated as millions of years, and a direct consideration of the presence of waves and wave parameters is highly challenging. In the current state-of-the-art, geodynamics and seismology cannot provide any other solution yet.The third section presents a solution considering record of deformation waves in the lithosphere. With account of the fact that all the earthquakes with М≥3.0 are associated with fault zones, a brief description of the method for assessment of spatial and temporal regularities in locations of earthquake epicentres in zones of dynamic influence of faults is provided. The method can be applied to estimate a dominating direction of movement of the epicentres, which corresponds to the phase velocity of the deformation wave disturbing meta-stability of the fault-block medium, leading to displacement of neighbouring blocks and thus causing a seismic event (Fig. 14). By integration of vectors of migration of epicentres at active faults, it is possible to demonstrate a pattern of vectors of movements of the deformation waves in the seismic zones of the continental lithosphere (Fig. 18).Regional and trans-regional deformation waves are analyzed. For seismic zones of Central Asia, vectors of deformation waves are established, a scheme showing regional orientations of the waves is developed, and main wave parameters (length and time period) are estimated (Fig. 19). Three depth levels of deformation waves are distinguished: the whole lithosphere, the upper brittle part of the lithosphere, and the top part of the brittle layer (Fig. 20).It is concluded that the leading factor of gradual accumulation of earthquake foci, which takes place regularly in space and time in seismic zones, are deformation waves that influence the geophysical medium. This understanding of the fundamental basis of seismic process needs to be more thoroughly justified with application of modern concepts, its revised phenomenological concept and development of a model representing a seismic zones as a geologically and geophysically independent structure of the lithosphere, which has its specific properties, based on which testing of the lithosphere becomes possible for purposes of potential earthquake prediction.